1998
DOI: 10.1207/s15327957pspr0201_4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression as a Stereotype Control Strategy

Abstract: Recent research reveals that efforts to suppress stereotypic thoughts can backfire and produce a rebound effect, such that stereotypic thinking increases to a level that is even greater than if no attempt at stereotype control was initially exercised (e.g., Macrae, Bodenhausen, Milne, & Jetten, 1994). The primary goal of this article is to present an in-depth theoretical analysis of stereotype suppression that identifies numerous potential moderators of the effect of stereotype suppression on the likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
1
13

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(186 citation statements)
references
References 56 publications
9
163
1
13
Order By: Relevance
“…Prior research has well documented that low-prejudice people are more willing and/or able to inhibit their stereotypes than are high-prejudice people (e.g., Devine, 1989;Monteith, 1993;Monteith et al, 1998). In the present studies, prejudice also has been shown to influence processes as diverse as attention, interpretation, and integration of behavioral information.…”
Section: Inhibition Encoding and Integration Processessupporting
confidence: 56%
“…Prior research has well documented that low-prejudice people are more willing and/or able to inhibit their stereotypes than are high-prejudice people (e.g., Devine, 1989;Monteith, 1993;Monteith et al, 1998). In the present studies, prejudice also has been shown to influence processes as diverse as attention, interpretation, and integration of behavioral information.…”
Section: Inhibition Encoding and Integration Processessupporting
confidence: 56%
“…Devine's studies of efforts to change stereotypes in the laboratory indicate that they are governed by automatic processing. Controlled processing can alter cognitive responses, but the process involves first an automatic stereotyped response, which is then suppressed and overridden by a nonstereotyped response (Monteith, Sherman, & Devine, 1998). Stereotypes thus have a strong and lasting imprint on the individual, one that can be suppressed and overridden but which seems more difficult to extinguish altogether.…”
Section: Basic Researchmentioning
confidence: 99%
“…For example, in the case of prejudice, a person may have an automatic tendency to judge an outgroup member in a negative manner or an ingroup member in a positive manner but control the expression of those automatic tendencies for a variety of reasons (Monteith et al, 1998;Sherman, in press). In other words, automatic associations may not be expressed because of controlled processing.…”
Section: Introductionmentioning
confidence: 99%